KAJIAN FILSAFAT ILMU DAN FILSAFAT PENDIDIKAN TENTANG RELATIVISME KULTURAL DALAM PERSPEKTIF FILSAFAT MORAL - Satrijo Budiwibowo (Universitas PGRI Madiun, 2012)
Pedagogics as the mainstream in edication, requires practical notions generated from phylosophy so that the contents can fulfil conceptual and functional substances. Phylosophy proposes questions and search for reality and experience which are usually found in educational practice. Phylosophy and education are interrelated, where problems of education and those of phylosophy belong to the same area. The development of conceptual frameworks is spawned by phylosophy. Educational phylosophy bears schools as naturalism, idealism, realism, pragmatism, progressivism, esentialism and perenialism. Morality has become a set of rules of the way people mutually need the others, rationally receive for the sake of mutual benefits in the obedience of the rules. The most crucial problem of social contract is the mutual trust against others,obedience of rules, except in a very specific condition.